2020
DOI: 10.1097/sla.0000000000004675
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Management, and Outcomes Related to Preoperative Medical Orders for Life Sustaining Treatment (MOLST) in an Adult Surgical Population

Abstract: Objective: To determine prevalence of documented preoperative code status discussions and postoperative outcomes (specifically mortality, readmission, and discharge disposition) of patients with completed MOLST forms before surgery. Summary of Background Data: A MOLST form documents patient care preference regarding treatment limitations. When considering surgery in these patients, preoperative discussion is necessary to ensure concordance of care. Little is known about prevalence of these discussions and post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In our cohort, 77% of patients had a discussion on assigning or confirming a designated HCP, and 15% of patients had a MOLST form completed during the visit. Although these rates are lower than other domains discussed in the CGA, it was higher than expected, as a recent study showed that less than 2% of older patients undergoing elective surgery had a completed MOLST form documented 40 . This further emphasizes the importance of discussing and documenting patients' preferences, trade‐offs, priorities, and expected treatment goals, 41–43 specifically, as the American College of Surgeons and the American Geriatric Society have launched the Geriatric‐Surgery Verification program, requiring these discussions to be explicitly documented in the EHR 44 …”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In our cohort, 77% of patients had a discussion on assigning or confirming a designated HCP, and 15% of patients had a MOLST form completed during the visit. Although these rates are lower than other domains discussed in the CGA, it was higher than expected, as a recent study showed that less than 2% of older patients undergoing elective surgery had a completed MOLST form documented 40 . This further emphasizes the importance of discussing and documenting patients' preferences, trade‐offs, priorities, and expected treatment goals, 41–43 specifically, as the American College of Surgeons and the American Geriatric Society have launched the Geriatric‐Surgery Verification program, requiring these discussions to be explicitly documented in the EHR 44 …”
Section: Discussionmentioning
confidence: 66%
“…Although these rates are lower than other domains discussed in the CGA, it was higher than expected, as a recent study showed that less than 2% of older patients undergoing elective surgery had a completed MOLST form documented. 40 F I G U R E 2 Distribution of the length of stay (LOS) among those without and with frailty.…”
Section: Discussionmentioning
confidence: 99%
“…Our own work shows that there are significant discrepancies in the documentation of code status restrictions, and in some cases, the clinical care provided may not align correctly with what the patient actually wants. 14 We found that fewer than half of surgical patients with preoperative MOLST (Medical Orders for Life Sustaining Treatment) had documented code status discussions before surgery. Ensuring compliance with ACS GSV standards could go a long way toward ensuring appropriate documentation of code status, limitations on resuscitation, and discussions regarding perioperative management of patients with restrictions on resuscitation.…”
Section: Geriatric Surgery Centers and The Acs Gsv Certification Programmentioning
confidence: 83%
“…The impact of the ACS GSV on cancellations and delays of surgery, as well as validation of alignment of patient goals and values with surgical goals also is an important area of future investigation. Our own work shows that there are significant discrepancies in the documentation of code status restrictions, and in some cases, the clinical care provided may not align correctly with what the patient actually wants 14. We found that fewer than half of surgical patients with preoperative MOLST (Medical Orders for Life Sustaining Treatment) had documented code status discussions before surgery.…”
Section: Geriatric Surgery Centers and The Acs Gsv Certification Programmentioning
confidence: 89%